Body composition in patients with heart failure - O. M. Drapkina; I. A. Skripnikova; E. K. Yaralieva; R. P. Myasnikov (Кардиоваскулярная терапия и профилактика, 2023)
The redistribution of body composition components in heart failure (CHF) is an urgent and poorly understood issue. Despite the significant impact of a decrease in muscle mass, redistribution of fat mass on the course and prognosis of HF, body composition is rarely taken into account in the treatment of this disease. In this regard, the purpose of this review was to systematize the available data and draw the attention of clinicians to this problem. The data presented in the review make it possible to consider the components of body composition as controllable factors, the normalization of which improves the prognosis in patients with HF. The study of pathophysiological mechanisms for the development of body composition anomalies in HF will make it possible to search for new therapeutic targets. Assessment of body composition will make it possible to develop an individual strategy for the treatment of HF, including a set of non-drug measures.